DYNAMICS OF SOCIAL LIFE OF LAISA'S FAMILY IN TERE LIYE’S "DIA ADALAH KAKAKKU" - Farida, Anisatul; Zawawi, Moh (Annual International Conferences on Language, Literature, and Media, 2022)
This study aims to describe the portrait of a family's life in the novel "Dia adalah Kakakku" by Tere Liye, published in 2018. This research is a type of descriptive qualitative research. The primary data source of this research is the novel "Dia adalah Kakakku" by Tere Liye, while the secondary data sources are sociological theory books, especially Karl Marx's sociology, journals, theses, and other supporting reading books. The data collection technique in this study used reading and note-taking techniques with the Sociological Karl Max approach model. The data analysis used in this study is the Miles and Huberman model through three stages: data reduction, data exposure, and drawing conclusions. The sociological theory of Karl Marx says that the main driving factor of all social change is the economy. The results of this study indicate the discovery of the phenomenon of the relationship between hard work with humans and the economy as an essential factor in the dynamics of social life in the novel " Dia adalah Kakakku".